PV Power-Generation System with a Phase-Shift PWM Technique for High Step-Up Voltage Applications - Cheng-Tao Tsai; Sin-Hua Chen (International Journal of Photoenergy)
A PV power-generation system with a phase-shift pulse-width modulation (PWM) technique for high step-up voltage applications is proposed. The proposed power-generation system consists of two stages. In the input stage, all power switches of the full-bridge converter with phase-shift technique can be operated with zero-current switching (ZCS) at turn-on or turn-off transition. Hence, the switching losses of the power switches can be reduced. Then, in the DC output stage, a voltage-doubler circuit is used to boost a high dc-link bus voltage. To supply a utility power, a dc/ac inverter is connected to induce a sinusoidal source. In order to draw a maximum power from PV arrays source, a microcontroller is incorporated with the perturbation and observation method to implement maximum power point tracking (MPPT) algorithm and power regulating scheme. In this study, a full load power of 300 W prototype has been built. Experimental results are presented to verify the performance and feasibility of the proposed PV power-generation system.